Carfilzomib significantly improves the progression-free survival of high-risk patients in multiple myeloma - Avet-Loiseau, Hervé; Fonseca, Rafael; Siegel, David; Dimopoulos, Meletios A; Špička, Ivan; Masszi, Tamás; Hájek, Roman; Rosiñol, Laura; Goranova-Marinova, Vesselina; Mihaylov, Georgi; Maisnar, Vladimír; Mateos, Maria-Victoria; et al. (Blood, 2016)
The presence of certain high-risk cytogenetic abnormalities, such as translocations (4;14) and (14;16) and deletion (17p), are known to have a negative impact on survival in multiple myeloma (MM). The phase 3 study ASPIRE (N = 792) demonstrated that progression-free survival (PFS) was significantly improved with carfilzomib, lenalidomide, and dexamethasone (KRd), compared with lenalidomide and dexamethasone (Rd) in relapsed MM. This preplanned subgroup analysis of ASPIRE was conducted to evaluate KRd vs Rd by baseline cytogenetics according to fluorescence in situ hybridization. Of 417 patients with known cytogenetic risk status, 100 patients (24%) were categorized with high-risk cytogenetics (KRd, n = 48; Rd, n = 52) and 317 (76%) were categorized with standard-risk cytogenetics (KRd, n = 147; Rd, n = 170). For patients with high-risk cytogenetics, treatment with KRd resulted in a median PFS of 23.1 months, a 9-month improvement relative to treatment with Rd. For patients with standard-risk cytogenetics, treatment with KRd led to a 10-month improvement in median PFS vs Rd. The overall response rates for KRd vs Rd were 79.2% vs 59.6% (high-risk cytogenetics) and 91.2% vs 73.5% (standard-risk cytogenetics); approximately fivefold as many patients with high- or standard-risk cytogenetics achieved a complete response or better with KRd vs Rd (29.2% vs 5.8% and 38.1% vs 6.5%, respectively). KRd improved but did not abrogate the poor prognosis associated with high-risk cytogenetics. This regimen had a favorable benefit-risk profile in patients with relapsed MM, irrespective of cytogenetic risk status, and should be considered a standard of care in these patients. This trial was registered at www.clinicaltrials.gov as #NCT01080391.
Keywords: Thalidomide; recidiva; dexamethason; Humans; lidé středního věku; Risk Factors; Oligopeptides; Multiple Myeloma; Female; rizikové faktory; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; senioři; lidé; přežití bez známek nemoci; oligopeptidy; mnohočetný myelom; Adult; Lenalidomide; ženské pohlaví; Male; Middle Aged; Adolescent; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Recurrence; Disease-Free Survival; míra přežití; mužské pohlaví; lenalidomid; mladiství; thalidomid; Survival Rate